Implementasi model pembelajaran konstruktivisme untuk meningkatkan kemampuan pemahaman matematika siswa - Jojo Johari; Uba Umbara; Evan Farhan Wahyu Puadi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
Observations conducted by researchers in one of class VII showed that the ability of students' understanding in the class is still minus. Whereas in KTSP 2013 mentioned that mathematical understanding is one of the basic competencies that must be owned and developed by students in learning mathematics. Based on the problem, the research was conducted by implementing constructivism model of learning in mathematics learning. Constructivism is one of the learning model where the students are actively mentally build their own knowledge based on the cognitive structure they have. This study is a classroom action research (PTK) carried out at SMPN 1 Lebakwangi. To obtain data in this study, the instruments used are the ability of comprehension test, observation sheet and student response questionnaire. Tests are tested with validity, reliability of difficulty levels and distinguishing power. The collected data is analyzed descriptively and quantitatively. Through the test obtained at each end of the cycle obtained the results of cycle I 45.75%, cycle II 65, 71%, and cycle III 85, 71%. From the results of this study also shows that learning mathematics with constructivism learning model can improve students' understanding ability. The best improvement is achieved on the aspect of the ability to transform a form of representation to another and the ability to recognize the various meanings and interpretations of concepts. This is seen from the calculation of the gain index is 0.29 with the medium category. Besides from result of questionnaire of student response showed positive response from student at learning by using constructivism learning model. This is seen from the results of the questionnaire calculation with the majority of students answered the response agreed 46, 38%.